Ketahanan Pangan, Pola Konsumsi Pangan, dan Peran Ibu pada Keluarga yang Memiliki Balita di Daerah Lokus Stunting dan Non Lokus di Kabupaten Lombok Timur, Nusa Tenggara Barat: Food Security, Dietary Practices, and Maternal Roles among Households with Children Under Five in Stunting Locus and Non Locus Areas in East Lombok District, Indonesia - Lalu Juntra Utama; I Nyoman Adiyasa; Ni Ketut Sri Sulendri; Luh Suranadi (Universitas Airlangga, 2026)
Background: Food security is a fundamental challenge to improving the health of children and adolescents. West Nusa Tenggara (NTB) Province, Indonesia, and East Lombok Regency face child nutrition issues, with one in three under-fives suffering from stunting linked to food security. Objectives: This study will analyse food security, dietary patterns, and the role of mothers with under-fives in stunting-prone and non-stunting-prone areas. Methods: A cross-sectional study involving 228 families with children under five years of age. Data collected included maternal characteristics (age, education, occupation, income and nutritional status) and child characteristics (age, sex, nutritional status and health status, maternal knowledge level, dietary patterns, household food security and data on the mother’s role in infant care). Maternal nutritional status was determined using BMI-for-age, whilst infant nutritional status was determined using weight-for-age, height-for-age and weight-for-height indices. Data analysis was performed using the chi-square test and t-test. Results: A total of 59.7% of mothers were overweight and 64.0% of children were underweight. Families with varying levels of vulnerability (mild, moderate and severe) accounted for 75.0%, whilst only 25.0% were food secure; 71.1% of families had inadequate dietary patterns, and 54.4% of mothers practised good childcare practices. There was a significant difference between mothers’ knowledge, parenting practices and household food security (p-value<0.001). Conclusions: A mother’s role in her child’s upbringing determines the child’s nutritional status. This upbringing encompasses appropriate feeding, health monitoring and emotional support. Strengthening the mother’s role in her child’s health could serve as a strategy to reduce stunting rates.